Organic fluorescent material and application thereof in preparation of perovskite-crystalline silicon laminated solar cell

By using organic fluorescent materials to incorporate perovskite absorbing layers in perovskite-crystalline silicon stacked solar cells, the destructive problem of ultraviolet light on perovskite materials is solved, the photoelectric conversion efficiency is improved and the battery preparation process is simplified , realizes a low-cost solution.

CN119285620AActive Publication Date: 2025-01-10上海恒羲光伏科技有限公司 +1

Patent Information

Application Number
CN202411418142.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing ultraviolet absorption technology is destructive to perovskite solar cell materials, resulting in device failure, and the light-to-film technology increases the manufacturing cost and process complexity of the battery. How to avoid ultraviolet light damage at low cost and improve the photoelectric conversion efficiency is Problems that the industry needs to solve urgently.

Method used

An organic fluorescent material is used to incorporate it into the perovskite absorber layer, and a perovskite solution-converting material compound solution is formed by compounding it with the perovskite film precursor solution, which is used for the perovskite-crystalline silicon stack The preparation of solar cells avoids ultraviolet light damage and improves visible light absorption and conversion efficiency, simplifies process steps.

Benefits of technology

It effectively avoids damage to perovskites by ultraviolet light, improves the photoelectric conversion efficiency of solar cells, simplifies the battery preparation process, and reduces the need for additional photo-to-film functional layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285620A_ABST
    Figure CN119285620A_ABST
Patent Text Reader

Abstract

The invention provides an organic fluorescent material and application thereof in preparation of a perovskite-crystalline silicon laminated solar cell, and the molecular formula of the organic fluorescent material is # imgabs0. In the preparation process of the perovskite-crystalline silicon laminated solar cell, the organic fluorescent material is added into a perovskite thin film precursor solution, and the perovskite thin film precursor solution is prepared into the perovskite thin film. According to the invention, the perovskite solution and the conversion material are prepared into a perovskite solution-conversion material compound solution, the perovskite solution-conversion material compound solution is used for coating a perovskite light absorption layer, the damage of ultraviolet light to perovskite can be avoided, the perovskite can also absorb emitted visible light and generate electricity, and the photoelectric conversion efficiency of the cell is improved; the light conversion film functional layer does not need to be additionally made, and the cell preparation process steps are simplified. In addition, the organic fluorescent material is used as an additive, crystal defects in the perovskite light absorption layer can be passivated, the quality of the perovskite thin film is improved, the service life of a carrier is prolonged, and the photoelectric conversion performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to an organic fluorescent material and an application thereof in the preparation of a perovskite-crystalline silicon stacked solar cell. Background Art

[0002] Perovskite solar cells are considered to be the most promising technology in the new generation of thin-film solar cells due to their excellent photoelectric properties, simple preparation process and low cost. At the same time, perovskite materials can easily change their band gaps by regulating their components, and their preparation methods are also diverse. Therefore, perovskite solar cells are widely used to prepare stacked cells, breaking the Shockley–Queisser limit (SQ limit) of single-cell cells and further improving the photoelectric conversion efficiency of solar cells. However, ultraviolet light in the solar spectrum is highly destructive to perovskite materials, which can easily cause degradation and phase change of perovskites, leading to device failure. Existing ultraviolet light absorption technology directly absorbs it, and solar cells cannot use the energy of ultraviolet light to generate electricity; light transfer film technology will cause additional process complexity and increase the cost of battery manufacturing. How to use convenient methods to avoid ultraviolet light damage to perovskites at a low cost and ensure the photoelectric conversion efficiency of batteries is a technical problem that the industry urgently needs to solve. Summary of the invention

[0003] The purpose of the present invention is to provide an organic fluorescent material and its application in the preparation of perovskite-crystalline silicon stacked solar cells. The organic fluorescent material is added to the perovskite light absorption layer to avoid ultraviolet light damage to the perovskite, while the perovskite can also absorb the emitted visible light and generate electricity, thereby improving the photoelectric conversion efficiency of the battery; there is no need to make an additional light transfer film functional layer, simplifying the battery preparation process steps.

[0004] In order to achieve the above purpose, this application adopts the following technical solutions:

[0005] In a first aspect, the present invention provides an organic fluorescent material, the molecular formula of the organic fluorescent material is as follows:

[0006]

[0007] In a second aspect, the present invention provides a method for preparing the above-mentioned organic fluorescent material, wherein the organic fluorescent material is prepared by using CA1 and CA2 molecules as raw materials, tetrahydrofuran as a reaction solvent, reacting at 25°C, and purifying through a silica gel chromatography column after the reaction is completed;

[0008] The molecular formulas of CA1 and CA2 are as follows:

[0009]

[0010] In a second aspect, the present invention provides the use of the above-mentioned organic fluorescent material in the preparation of perovskite-crystalline silicon tandem solar cells.

[0011] In the above technical solution, during the preparation of perovskite-crystalline silicon stacked solar cells, the organic fluorescent material is added to the perovskite film precursor solution to prepare a perovskite solution-conversion material composite solution for coating the perovskite light absorbing layer.

[0012] In a third aspect, the present invention provides a perovskite solution-conversion material composite solution, wherein the perovskite solution-conversion material composite solution comprises a perovskite film precursor solution and the above-mentioned organic fluorescent material.

[0013] In the above technical solution, the concentration of the organic fluorescent material in the perovskite solution-conversion material composite solution is between 0.5 and 3 mg / ml.

[0014] In the above technical scheme, the perovskite components in the perovskite film precursor solution are rubidium iodide, cesium iodide, methylamine bromide, formamidinium iodide and lead iodide in a molar ratio of 0.02-0.05: 0.02-0.05: 0.02-0.05: (0.85-0.88): (0.85-0.9), the total molar concentration of the perovskite components is 1.2-1.5 mol / L, and the solvent is a mixed solvent of DMF and DMSO in a volume ratio of (4-6):1.

[0015] In a fourth aspect, the present invention provides a perovskite-crystalline silicon tandem solar cell, wherein the perovskite-crystalline silicon tandem solar cell comprises a perovskite light-absorbing layer, wherein the perovskite light-absorbing layer is formed by coating a perovskite solution-conversion material composite solution, wherein the perovskite solution-conversion material composite solution comprises a perovskite thin film precursor solution and the organic fluorescent material according to claim 1.

[0016] In the above technical scheme, the perovskite-crystalline silicon stacked solar cell includes a Si bottom cell, a transparent conductive composite layer, a hole transport layer, a perovskite light absorption layer, a post-processing layer, a first electron transport layer, a second electron transport layer, a transparent conductive film layer and an anti-reflection layer stacked in sequence from bottom to top.

[0017] In the above technical solution, the method for preparing the perovskite-crystalline silicon tandem solar cell comprises the following steps:

[0018] Step 1: using PVD magnetron sputtering technology to plate a TCO transparent conductive substrate on the Si bottom cell, or using RPD evaporation technology to deposit a TCO transparent conductive substrate, or using a combination of the two technologies to form the transparent conductive composite layer;

[0019] Step 2: performing an O2-plasma treatment on the transparent conductive composite layer for 4 minutes to remove organic matter remaining on the surface of the transparent conductive composite layer and improve the work function;

[0020] Step 3: coating the hole transport layer, using Me-4PACz) at a concentration of 0.5-1 mg ml-1, using ethanol as the solvent, and the spin coating process is 3000 (3000)*30s, followed by annealing at 100°C for 5-8min;

[0021] Step 4: coating the perovskite light absorbing layer, using the perovskite solution-conversion material composite solution, the coating process is 2000 (2000) * 10s + 5000 (5000) * 30s, adding 150 μL of chlorobenzene as an anti-solvent at 25 to 30 seconds, and then annealing at 85 to 100° C. for 10 to 15 minutes;

[0022] Step 5: coating the post-treatment layer, using PEAI post-treatment salt, the solution concentration is 1-2 mg ml-1, the solvent is isopropanol, the spin coating process is 4000 (4000) * 30s, followed by annealing at 100°C for 5-8min;

[0023] Step 6: Deposition of the first electron transport layer, C60 thermal evaporation, deposition rate 0.1-0.2 nm / s, deposition 35-50 nm;

[0024] Step 7: Deposition of the second electron transport layer, atomic layer deposition to prepare SnO 2 , using tetraethyltin as a precursor, deposited for 250 cycles, with a thickness of about 20 to 30 nm;

[0025] Step 8: Preparation of transparent conductive film layer, magnetron sputtering technology to plate ITO transparent conductive electrode, the sputtering target is ITO, the sputtering power is 150W, the sputtering time is 10min, and the obtained ITO thickness is about 120nm±10nm;

[0026] Step nine: evaporating silver as metal grid lines;

[0027] Step 10: Vapor-deposit MgF2 as the anti-reflection layer.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention incorporates a newly designed organic fluorescent material that absorbs ultraviolet light and emits visible light into the perovskite light-absorbing layer, thereby preventing ultraviolet light from damaging the perovskite. At the same time, the perovskite can also absorb the emitted visible light and generate electricity, thereby improving the photoelectric conversion efficiency of the battery. There is no need to make an additional light-conversion film functional layer, which simplifies the battery preparation process steps.

[0030] 2. The organic fluorescent material of the present invention, as an additive, can passivate the crystal defects in the perovskite light-absorbing layer, improve the quality of the perovskite film, increase its carrier lifetime, and improve the photoelectric conversion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a schematic diagram of the solar cell structure of the present invention;

[0033] Among them: 1. Si bottom battery; 2. Transparent conductive composite layer; 3. Hole transport layer; 4. Perovskite light absorption layer; 5. Post-processing layer; 6. First electron transport layer; 7. Second electron transport layer; 8. Transparent conductive film layer; 9. Anti-reflection layer. DETAILED DESCRIPTION

[0034] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.

[0035] The following describes the embodiments of the present disclosure through specific examples, and those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present disclosure.

[0036] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0037] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present disclosure. The drawings only show components related to the present disclosure rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0038] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.

[0039] The present invention provides a new organic fluorescent material, the molecular formula of which is as follows:

[0040]

[0041] Synthesis method: The organic fluorescent material is prepared by using CA1 and CA2 molecules as raw materials and tetrahydrofuran as a reaction solvent, reacting at 25°C for 1 hour and then purifying through a silica gel chromatography column.

[0042] The molecular formulas of CA1 and CA2 are as follows:

[0043]

[0044] Mechanism of action: The group represented by CA1 has the effect of absorbing ultraviolet light, which is transferred to the CA2 part through intramolecular energy relaxation and then emits light.

[0045] Based on this, the present invention applies the organic fluorescent material to the preparation of perovskite-crystalline silicon tandem solar cells. Before depositing the perovskite film, the self-designed organic fluorescent material is added to the perovskite film precursor solution. The molecule can efficiently convert ultraviolet light into near-infrared light. Through molecular structure design, the common and inexpensive molecule coumarin (pure coumarin absorbs ultraviolet light and emits blue light, which does not meet the use requirements of tandem cells) can absorb ultraviolet light and emit infrared light after chemical modification designed by us, thereby meeting the use requirements of tandem cells and reducing the loss of perovskite materials after being irradiated by high-energy photons.

[0046] As one embodiment, the organic fluorescent material is formulated into a perovskite solution-conversion material composite solution. The perovskite solution-conversion material composite solution includes a perovskite film precursor solution and an organic fluorescent material. The perovskite component in the perovskite film precursor solution is rubidium iodide, cesium iodide, methylamine bromide, formamidine iodine and lead iodide in a molar ratio of 0.05:0.05:0.05:0.85:1, the total molar concentration of the perovskite component is 1.4 mol / L, and the solvent is a mixed solvent of DMF and DMSO in a volume ratio of 4:1. The concentration of the organic fluorescent material is 1 mg / ml.

[0047] The perovskite solution-conversion material composite solution prepared by using the organic fluorescent material can be used to prepare the perovskite light-absorbing layer of the perovskite-crystalline silicon stacked solar cell.

[0048] As one embodiment, the perovskite-crystalline silicon stacked solar cell includes a Si bottom cell 1, a transparent conductive composite layer 2, a hole transport layer 3, a perovskite light absorption layer 4, a post-processing layer 5, a first electron transport layer 6, a second electron transport layer 7, a transparent conductive film layer 8 and an anti-reflection layer 9 stacked in sequence from bottom to top. The preparation method thereof includes the following steps:

[0049] Step 1: Use PVD (Physical Vapor Deposition magnetron sputtering technology) to plate a TCO transparent conductive substrate (such as ITO, i.e. Indium Tin Oxide film, or AZO, Aluminum-Doped Zinc Oxide film) on the Si bottom battery 1, or use RPD (Rapid Prototype Deposition evaporation technology) to deposit a TCO transparent conductive substrate (such as IWO, i.e. Indium Tungsten Oxide, or ICO, i.e. Indium Cadmium Oxide film) to form a transparent conductive composite layer 2.

[0050] If PVD technology is used, the sputtering target is ITO, the sputtering power is 150W, the sputtering time is 8min, and the obtained ITO thickness is 80-100nm. The above technologies can be mixed and matched to deposit composite film layers for adjusting electrical and optical properties.

[0051] Step 2: Performing O2-plasma treatment on the transparent conductive composite layer 2 for 4 minutes to remove residual organic matter on the surface of the transparent conductive composite layer 2 and improve the work function, reduce the battery recombination center, and improve the optical light transmission performance;

[0052] Step 3: coating of the hole transport layer 3, using Me-4PACz) at a concentration of 0.5-1 mg ml-1, using ethanol as the solvent, and the spin coating process is 3000 (3000)*30s, followed by annealing at 100°C for 5-8min;

[0053] Step 4: coating the perovskite light absorbing layer 4, using the perovskite solution-conversion material composite solution, the coating process is 2000 (2000) * 10s + 5000 (5000) * 30s, adding 150 μL of chlorobenzene as an anti-solvent at 25 to 30 seconds, and then annealing at 85 to 100° C. for 10 to 15 minutes;

[0054] Step 5: coating of post-treatment layer 5, using PEAI post-treatment salt, solution concentration of 1-2 mg ml-1, solvent is isopropanol, spin coating process is 4000 (4000) * 30s, followed by annealing at 100°C for 5-8min;

[0055] Step 6: Deposition of the first electron transport layer 6, C60 thermal evaporation, deposition rate 0.1-0.2 nm / s, deposition 35-50 nm;

[0056] Step 7: Deposition of the second electron transport layer 7, preparation of SnO by atomic layer deposition 2 , using tetraethyltin as a precursor, deposited for 250 cycles, with a thickness of about 20 to 30 nm;

[0057] Step 8: Preparation of transparent conductive film layer 8, magnetron sputtering technology is used to plate ITO transparent conductive electrode, the sputtering target is ITO, the sputtering power is 150W, the sputtering time is 10min, and the obtained ITO thickness is about 120nm±10nm;

[0058] Step nine: evaporating silver as metal grid lines;

[0059] Step 10: Vapor-deposit MgF2 as the anti-reflection layer 9.

[0060] Experimental procedures

[0061] The experimental group used the above preparation method to prepare perovskite-crystalline silicon stacked solar cells, and the control group used perovskite thin film precursor liquid (without organic fluorescent material) in step 4 to coat the perovskite light-absorbing layer, and the other steps remained unchanged. After the perovskite-crystalline silicon stacked solar cells were prepared, the cell efficiency, open circuit voltage, short circuit current, and ultraviolet light stability tests were conducted, and the test results are as follows:

[0062] Battery performance test results

[0063]

[0064] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An organic fluorescent material, characterized in that: The molecular formula of the organic fluorescent material is as follows:

2. A method for preparing the organic fluorescent material according to claim 1, characterized in that: The organic fluorescent material is prepared by using CA1 and CA2 molecules as raw materials, tetrahydrofuran as a reaction solvent, reacting at 25°C, and purifying through a silica gel chromatography column after the reaction. The molecular formulas of CA1 and CA2 are as follows:

3. Use of the organic fluorescent material according to claim 1 in the preparation of perovskite-crystalline silicon tandem solar cells.

4. The application according to claim 3, characterized in that: In the process of preparing perovskite-crystalline silicon stacked solar cells, the organic fluorescent material is added to the perovskite film precursor solution to prepare a perovskite solution-conversion material composite solution for coating the perovskite light absorbing layer.

5. A perovskite solution-conversion material composite solution, characterized in that: The perovskite solution-conversion material composite solution comprises a perovskite film precursor solution and the organic fluorescent material according to claim 1.

6. The perovskite solution-conversion material composite solution according to claim 5, characterized in that: The concentration of the organic fluorescent material in the perovskite solution-conversion material composite solution is between 0.5 and 3 mg / ml.

7. The perovskite solution-conversion material composite solution according to claim 5, characterized in that: The perovskite components in the perovskite film precursor solution are rubidium iodide, cesium iodide, methylamine bromide, formamidine iodine and lead iodide in a molar ratio of 0.02-0.05:0.02-0.05:0.02-0.05:(0.85-0.88):(0.85-0.9), the total molar concentration of the perovskite components is 1.2-1.5 mol / L, and the solvent is a mixed solvent of DMF and DMSO in a volume ratio of (4-6):

1.

8. A perovskite-crystalline silicon tandem solar cell, characterized in that: The perovskite-crystalline silicon stacked solar cell includes a perovskite light-absorbing layer, which is formed by coating a perovskite solution-conversion material composite solution, and the perovskite solution-conversion material composite solution includes a perovskite film precursor solution and the organic fluorescent material according to claim 1.

9. The perovskite-crystalline silicon tandem solar cell according to claim 8, characterized in that: The perovskite-crystalline silicon stacked solar cell comprises a Si bottom cell (1), a transparent conductive composite layer (2), a hole transport layer (3), a perovskite light absorption layer (4), a post-processing layer (5), a first electron transport layer (6), a second electron transport layer (7), a transparent conductive thin film layer (8) and an anti-reflection layer (9) which are stacked in sequence from bottom to top.

10. The perovskite-crystalline silicon tandem solar cell according to claim 9, characterized in that: The method for preparing the perovskite-crystalline silicon tandem solar cell comprises the following steps: Step 1: using PVD magnetron sputtering technology to plate a TCO transparent conductive substrate on the Si bottom cell (1), or using RPD evaporation technology to deposit a TCO transparent conductive substrate, or using a combination of the two technologies to form the transparent conductive composite layer (2); Step 2: performing an O2-plasma treatment on the transparent conductive composite layer (2) for 4 minutes, so as to remove organic matter remaining on the surface of the transparent conductive composite layer (2) and improve the work function; Step 3: coating the hole transport layer (3), using Me-4PACz) at a concentration of 0.5-1 mg ml-1, using ethanol as the solvent, and using a spin coating process of 3000 (3000)*30s, followed by annealing at 100°C for 5-8min; Step 4: coating the perovskite light absorbing layer (4) using the perovskite solution-conversion material composite solution, with a coating process of 2000 (2000) * 10s + 5000 (5000) * 30s, adding 150 μL of chlorobenzene as an anti-solvent at 25 to 30s, and then annealing at 85 to 100°C for 10 to 15 minutes; Step 5: coating the post-treatment layer (5) using PEAI post-treatment salt, the solution concentration is 1-2 mg ml-1, the solvent is isopropanol, the spin coating process is 4000 (4000)*30s, followed by annealing at 100°C for 5-8min; Step 6: Deposition of the first electron transport layer (6) by thermal evaporation of C60 at a deposition rate of 0.1 to 0.2 nm / s and a deposition thickness of 35 to 50 nm; Step 7: Deposition of the second electron transport layer (7): SnO2 is prepared by atomic layer deposition, using tetraethyltin as a precursor, and the deposition is repeated for 250 cycles, with a thickness of about 20 to 30 nm; Step 8: Preparation of transparent conductive film layer (8): ITO transparent conductive electrode is plated by magnetron sputtering technology, the sputtering target is ITO, the sputtering power is 150W, the sputtering time is 10min, and the obtained ITO thickness is about 120nm±10nm; Step nine: evaporating silver as metal grid lines; Step 10: Vapor-depositing MgF2 as the anti-reflection layer (9).

Citation Information

Patent Citations

  • Perovskite solar cell doped with glutamic acid coumarin derivative and preparation method thereof

    CN117098440A

  • Perovskite film layer passivator and preparation method and application thereof

    CN118125963A

  • Difunctional organic additive, perovskite light absorption layer precursor solution containing same and application of perovskite light absorption layer precursor solution

    CN118290391A

  • Bending Spacer for Deck-Plate and Deck Plate Manufacturing Method using the Same

    KR102306893B1

Cited By

  • Broadband-gap perovskite solar cell and preparation method thereof

    CN120166901A